Analysis of Patient Satisfaction and Quality of Life (OHRQoL) in Pulp Necrosis Patients After Root Canal Treatment - Yunita Styaningrum; Irma Dewi Ratnawati; Novi Sagita Rizky; Arlina Nurhapsari; Rizki Amalina; Davia Kurnia Akbar (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Pulp necrosis, a common dental issue, significantly impacts quality of life, making effective root canal treatment essential for addressing pain, infection, and psychological distress. This study aimed to analyze the relationship between patient satisfaction and Oral Health-Related Quality of Life (OHRQoL) following root canal treatment, providing insights to improve dental care and patient outcomes.Methods: This study employed a cross-sectional design, involving 118 patients with pulp necrosis who had completed root canal treatment at Sultan Agung Dental and Oral Hospital in Semarang. Data were collected using a validated patient satisfaction questionnaire and the OHIP-14 to assess Oral Health-Related Quality of Life (OHRQoL). Descriptive analysis and Spearman’s correlation test were used to evaluate demographic characteristics, satisfaction levels, and the relationship between satisfaction and OHRQoL, with significance set at p<0.05.Results: The study found that most respondents were female (59.3%), aged 26–35 years (35.6%), and held a diploma or bachelor's degree (53.4%), with an average high patient satisfaction score of 4.33 ± 0.6. Significant improvements in Oral Health-Related Quality of Life (OHRQoL) were observed after root canal treatment, with all OHIP-14 domain scores decreasing significantly (p < 0.001).Conclusion: The study concluded that the success of root canal treatment was closely linked to patient satisfaction and quality of life improvements, influenced by clinical effectiveness, dentist-patient interactions, and non-clinical factors like cost and accessibility.